Knowledge on gender dimensions of transportation in Portugal - Queirós, Margarida (2020)
Transport has been studied as gender neutral, as transportation services or infrastructures are considered to benefit all, men and women, evenly (Kunieda and Gauthier, 2007). However, surveys and statistical evidence reveals that the transport consumption between men and women is often gender blinded or gender biased. Until recently we knew little about gender differentiation in transport consumption in Portugal; as the EU gender policies develop, a deep effort is being made by Portuguese government to know more about gender mobility patterns1. This paper explores the statistical groundings on the transportation sector on gender inequalities in Portugal, and develops the discussion of the role that transport plays in the experience of men and women in daily mobility. It finally seeks to highlight possible gender transportation policy for future development. The overall research methodology was based on a review of the literature and in the analysis of national statistics on mobility concerning commuting displacement, separate by sex, by mode of transport and by travel time. After a brief review on the issue context, we present the main achievements of the research on the gender dimensions of transport in Portugal and demonstrate that women: 1) tend to take shorter trips, use more the public transport system and a have an additional complex trip chain, and 2) tend to use less the private car than men in daily use, revealing a more fragile condition concerning accessibility and mobility, in an urban form more and more shaped by the use of the car. The paper concludes that formal policy analysis in this domain should always be informed by gendered approaches as they demonstrate substantial differences among women and man’s patterns of mobility. Thus the effort to introduce the gender perspective into transport policy in Portugal is urgently required.